1992
DOI: 10.1007/bf01401113
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the cerebral vascular bed in experimental hydrocephalus: An angio-architectural and histological study

Abstract: The angio-architectural and histological changes of small cerebral blood vessels in experimental hydrocephalus were studied to assess the changes of the vascular bed in the cerebral mantle. Change of the microvasculature assessed from microcorrosion casts by scanning electron microscopy (SEM) and the histological changes shown by light and electron microscopy were compared before and after shunting for hydrocephalus. The changes of the rCBF were also evaluated by the hydrogen clearance method. In hydrocephalus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…In an animal study of experimental hydrocephalus, Rosenberg et al [36] have shown that increased intraventricular pressure leads to a significant reduction in cerebral blood flow, predominantly in periventricular tissue. Furthermore, a reduction in the number of capillaries has been observed following the induction of experimental hydrocephalus [37,38]. An additional mechanism has been suggested by the findings of Shapiro et al [31], who investigated a series of patients with severe fourth ventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 93%
“…In an animal study of experimental hydrocephalus, Rosenberg et al [36] have shown that increased intraventricular pressure leads to a significant reduction in cerebral blood flow, predominantly in periventricular tissue. Furthermore, a reduction in the number of capillaries has been observed following the induction of experimental hydrocephalus [37,38]. An additional mechanism has been suggested by the findings of Shapiro et al [31], who investigated a series of patients with severe fourth ventricular hemorrhage.…”
Section: Discussionmentioning
confidence: 93%
“…Despite their distance from the dilated ventricles, those vessels coming from the cortical surface will become distorted in an effort to supply the corresponding cerebral tissue [106]. Damage may compromise both peripheral and deep vessels.…”
Section: Cerebral Blood Vessels and Cerebral Blood Flowmentioning
confidence: 99%
“…We also showed decreased vascularity and CBF in frontal cortex after induced CH and have suggested that these changes may be related to increased ICP, decreased cardiac output, or mechanical compression[6, 7]. However, the blood vessel density changes in chronic hydrocephalus have been observed to be in both directions and hence cannot be explained by simple spatial compression[4, 6, 20]. In the current study, we further explored the underlying mechanisms and demonstrated decreased VEGFR-2 levels, correlating with decreased CBF in frontal cortex after CH induction.…”
Section: Discussionmentioning
confidence: 97%